Investigating the relationship between achievement motive and performance in elite-level football goalkeepers - Madsen, Esben Elholm; Hansen, Tina; Rafnsson, Dadi; Krustrup, Peter; Larsen, Carsten Hvid; Elbe, Anne-Marie (Scandinavian Journal of Sport and Exercise Psychology, 2024)
The goalkeeper position in football is highly specific. Investigating the achievement motive of elite-level goalkeepers might help football coaches in general, goalkeeping coaches, and sports psychologists to gain insight into and knowledge of the approaches needed for enhancing the performance of this unique position within the football team. This study aimed to examine the achievement motive for male goalkeepers playing at the elite level in Denmark (n = 34) and Iceland (n = 20) and to investigate the relationship between the achievement motive, age and performance. In addition to biographical questions, the study employed the Achievement Motives Scale – Sport. The findings from the present study suggest that goalkeepers are characterized by higher hope for success than fear of failure values, like other elite athletes, while younger goalkeepers had significantly higher fear of failure. There were no differences between starting and non-starting goalkeepers, but we found that performance level was associated with fear of failure when controlling for the goalkeeper’s status (starters versus non-starters) and playing country. Finally, goalkeepers playing in Denmark showed lower fear of failure than goalkeepers playing in Iceland. Implications for practice and future research are discussed.